Proceedings of the XII International Symposium on Biological Control of Weeds La Grande Motte, France, 22–27 April 2007 - Julien, M.H (CABI, 2014)
Understanding and modelling the population dynamics of weeds and/or biological control agents can require large investments of time and money; just what are we getting for our modelling efforts? Here I respond to three persistent critiques of modelling as used in biological control programmes and present new directions for extending and improving our use of models. Complex models have been critiqued as resource-intensive, too narrow in scope and difficult to analyse, whereas simple, strategic models are critiqued as oversimplified and inaccurate in predicting postinvasion population dynamics. I argue that models across this spectrum can be useful and that the dichotomy between simple and complex models can be broken down. Biological control practitioners often operate in systems with a high degree of stochasticity and uncertainty; therefore, the incorporation of stochasticity and uncertainty into population models is essential for the development of robust management strategies. Close dialogue between managers and modellers is essential for the application of modelling studies to management. New directions for modelling in biological control include the incorporation of invader impact and complex ecosystem effects such as habitat heterogeneity and disturbance. The right model used for the right question can bring us insights into the biological control process that would be difficult or impossible to achieve otherwise.